Wear-resistant modified polytetrafluoroethylene composite material and preparation method thereof
By filling Ga/Al-LDHs and PEEK in polytetrafluoroethylene, the problem of poor wear resistance of polytetrafluoroethylene is solved, and the effect of significantly reducing wear rate and maintaining mechanical properties is achieved.
Patent Information
- Application Number
- CN202411886772.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-20
- Publication Date
- 2025-03-11
- Estimated Expiration
- 2044-12-20
AI Technical Summary
Polytetrafluoroethylene materials have poor wear resistance, which limits their application range.
The frictional properties are enhanced by filling polytetrafluoroethylene with calcium-aluminum hydrotalcite (Ga/Al-LDHs) and polyether etherketone (PEEK) as synergistic fillers.
The wear rate of polytetrafluoroethylene composite material is significantly reduced, which is only 1/150 to 1/300 of pure polytetrafluoroethylene, while maintaining excellent mechanical properties.
Smart Images

Figure CN119591996A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of polymer material science, in particular to a wear-resistant modified polytetrafluoroethylene composite material and a preparation method thereof. Background Art
[0002] Polytetrafluoroethylene is corrosion-resistant and hardly reacts with strong acids and alkalis (concentrated sulfuric acid, caustic soda, aqua regia), strong oxidants (potassium permanganate, peroxide, potassium dichromate), etc. It is often used as a protective layer on metal surfaces; Polytetrafluoroethylene is an excellent insulator, its molecular chain is non-polar, and its dielectric properties are stable; Polytetrafluoroethylene is also resistant to high and low temperatures, and still maintains excellent mechanical properties in a wide temperature range of -190 to 260°C. Although polytetrafluoroethylene has a very low friction coefficient, its wear rate is relatively high, so the wear resistance of polytetrafluoroethylene is poor, which greatly limits the application of polytetrafluoroethylene.
[0003] Filling modification is to add functional fillers to polytetrafluoroethylene base resin for composite modification, thereby improving and overcoming the defects of polytetrafluoroethylene, and giving full play to the synergistic and complementary effects of two or more components on the basis of maintaining its original advantages. Therefore, the present invention adopts a filling modification method to enhance the friction performance of polytetrafluoroethylene composite materials, wherein the filler is composed of calcium aluminum hydrotalcite (Ga / Al-LDHs) and polyetheretherketone (PEEK). The filling modification can maximize its friction performance and prepare a highly wear-resistant polytetrafluoroethylene composite material. In addition, the present invention has the advantages of simple process, low cost, suitable for mass production, etc., which is conducive to industrial promotion. Summary of the invention
[0004] The present invention aims to provide a wear-resistant modified polytetrafluoroethylene composite material and a preparation method thereof, wherein the composite material uses Ga / Al-LDHs and PEEK as fillers, and the polytetrafluoroethylene composite material is prepared by synergistic filling. Another object of the present invention is to maintain the excellent mechanical properties of the polytetrafluoroethylene composite material.
[0005] The technical solution of the present invention is as follows:
[0006] A wear-resistant modified polytetrafluoroethylene composite material is prepared by polytetrafluoroethylene filled with Ga / Al-LDHs and PEEK modified materials; the Ga / Al-LDHs accounts for 1-12wt% of the total weight of the modified polytetrafluoroethylene composite material, the PEEK accounts for 5-50wt% of the total weight of the modified polytetrafluoroethylene composite material, and the polytetrafluoroethylene accounts for 94-38wt% of the total weight of the modified polytetrafluoroethylene composite material.
[0007] In the aforementioned wear-resistant modified polytetrafluoroethylene composite material, the Ga / Al-LDHs accounts for 1-8wt% of the total weight of the polytetrafluoroethylene composite material, the PEEK accounts for 10-54wt% of the total weight of the polytetrafluoroethylene composite material, and the polytetrafluoroethylene accounts for 89-38wt% of the total weight of the polytetrafluoroethylene composite material.
[0008] Specifically, in the aforementioned wear-resistant modified polytetrafluoroethylene composite material, the Ga / Al-LDHs accounts for 2-4wt% of the total weight of the polytetrafluoroethylene composite material, the PEEK accounts for 20-30wt% of the total weight of the polytetrafluoroethylene composite material, and the polytetrafluoroethylene accounts for 78-66wt% of the total weight of the polytetrafluoroethylene composite material.
[0009] The preparation method of the aforementioned wear-resistant modified polytetrafluoroethylene composite material is carried out according to the following steps:
[0010] (1) Mixing: polytetrafluoroethylene, Ga / Al-LDHs and PEEK are mixed by a high-speed mixer at 1000-1400 r / min for 15-25 minutes to obtain product A;
[0011] (2) Compression molding: Pour product A into a cold pressing mold and cold press the powder at room temperature at a pressure of 35 to 55 MPa for 10 to 30 minutes to obtain product B;
[0012] (3) Thermal sintering treatment: Place product B in a sintering furnace, raise the temperature from room temperature to 322-332°C at a heating rate of 0.5-1.5°C / min, and keep it at 322-332°C for 55-65 min. Then, raise the temperature to 370-380°C at a heating rate of 0.5-1.5°C / min and keep it at that temperature for 80-100 min. Then, lower the temperature from 370-380°C to 322-332°C at a cooling rate of 1-2°C / min and keep it at that temperature for 55-65 min. After the heat preservation is completed, turn off the power supply, let it cool naturally to room temperature, and then cut and prepare the sample to obtain a polytetrafluoroethylene composite material.
[0013] In the above step (1), mixing: polytetrafluoroethylene, Ga / Al-LDHs and PEEK are mixed by a high-speed mixer at 1200 r / min for 20 minutes to obtain product A.
[0014] In the above step (2), compression molding: Pour product A into a cold pressing mold, and cold press the powder at a pressure of 40 to 50 MPa for 15 to 25 minutes at room temperature to obtain product B.
[0015] In the above step (3), heat sintering treatment: take product B and place it in a sintering furnace, increase the temperature from room temperature to 327°C at a heating rate of 1°C / min, and keep it at 327°C for 60 minutes, then increase the temperature to 375°C at a heating rate of 1°C / min and keep it at that temperature for 90 minutes, then cool it from 375°C to 327°C at a cooling rate of 1.5°C / min and keep it at that temperature for 60 minutes, turn off the power after the insulation is completed, let it cool naturally to room temperature, and then cut and prepare samples to obtain a modified polytetrafluoroethylene composite material.
[0016] Compared with the prior art, the present invention has the following beneficial effects:
[0017] 1. The present invention uses Ga / Al-LDHs and PEEK as synergistic fillers to fill polytetrafluoroethylene composite materials. Ga / Al-LDHs enhances the surface, soft microfiller PEEK enhances the subsurface, and PTFE can achieve ultra-low wear rate through the combination of surface and subsurface enhancement. The wear rate of the polytetrafluoroethylene composite material filled with Ga / Al-LDHs and PEEK is only 1 / 150 to 1 / 300 of that of pure polytetrafluoroethylene, and the modified polytetrafluoroethylene composite material filled with Ga / Al-LDHs and PEEK has a lower friction coefficient.
[0018] 2. The modified polytetrafluoroethylene composite material filled with Ga / Al-LDHs and PEEK of the present invention can maintain the excellent mechanical properties of polytetrafluoroethylene.
[0019] 3. The present invention uses a filling and modification method to enhance the wear resistance of polytetrafluoroethylene, has a simple production process, and can realize industrial large-scale production. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 : Friction coefficient and wear rate of polytetrafluoroethylene composites with 0wt%, 1wt%, 2wt%, 4wt%, 8wt% and 12wt% of Ga / Al-LDHs and 20wt% of PEEK added respectively;
[0021] Figure 2 : Friction coefficient and wear rate of polytetrafluoroethylene composites with 0wt%, 5wt%, 10wt%, 20wt%, 30wt% and 50wt% PEEK and 4wt% Ga / Al-LDHs added respectively;
[0022] Figure 3 : Finished product pictures of pure polytetrafluoroethylene and polytetrafluoroethylene composite materials (A: pure polytetrafluoroethylene prepared in Example 1; B: polytetrafluoroethylene composite material prepared in Example 5). DETAILED DESCRIPTION
[0023] The present invention is described in detail below by way of examples. It is necessary to point out that the following examples are only used to further illustrate the present invention and are not to be construed as limiting the scope of protection of the present invention.
[0024] Embodiment 1:
[0025] Preparation of pure polytetrafluoroethylene: Pour polytetrafluoroethylene powder into a cold pressing mold, cold press the mixed powder at a pressure of 40 to 50 MPa for 15 to 25 minutes at room temperature, take the mixed powder out of the cold pressing mold after pressing, trim and remove burrs to make it smooth and flat, and obtain a composite material sheet. Place the composite material sheet in a sintering furnace for heat treatment, first increase the temperature of the sintering furnace from room temperature to 327°C at a heating rate of 1°C / min, and place the sample in Heat treatment was carried out at 327°C for 60 minutes; then the temperature was increased to 375°C at a heating rate of 1°C / min and kept at this temperature for 90 minutes; then the temperature was reduced from 375°C to 327°C at a cooling rate of 1.5°C / min and kept at this temperature for 60 minutes; finally, after the insulation was completed, the power was turned off and allowed to cool naturally to room temperature; after the furnace temperature cooled to room temperature, the heat-treated sheet was taken out of the furnace, and then a CNC machine tool was used to cut and prepare the sample to obtain a pure polytetrafluoroethylene test sample.
[0026] Embodiment 2:
[0027] Material ratio: 0wt% Ga / Al-LDHs, 20wt% PEEK and 80wt% polytetrafluoroethylene.
[0028] Preparation method of modified polytetrafluoroethylene composite material: PEEK is added to polytetrafluoroethylene for high-speed blending, and mixed at 1200r / min for 20 minutes by a high-speed mixer. Then the mixed powder is poured into a cold mold, and the powder is cold pressed at a pressure of 40-50MPa for 15-25min at room temperature. After the mixed powder is pressed, it is taken out of the cold mold, trimmed to remove burrs, and made smooth to obtain a composite sheet. Then it is placed in a sintering furnace for heat treatment. First, the temperature of the sintering furnace is increased from room temperature to 327°C at a heating rate of 1°C / min, and the sample is heat treated at 327°C for 60 minutes; then the temperature is increased to 375°C at a heating rate of 1°C / min and kept at this temperature for 90 minutes; then the temperature is cooled from 375°C to 327°C at a cooling rate of 1.5°C / min and kept at this temperature for 60 minutes; finally, after the insulation is completed, the power is turned off and the sample is allowed to cool naturally to room temperature; after the furnace temperature is cooled to room temperature, the heat-treated sheet is taken out of the furnace, and then a CNC machine tool is used to cut and prepare the sample to obtain a polytetrafluoroethylene composite material.
[0029] Embodiment 3:
[0030] Material ratio: 1wt% Ga / Al-LDHs, 20wt% PEEK and 79wt% polytetrafluoroethylene;
[0031] Preparation method of modified polytetrafluoroethylene composite material: Ga / Al-LDHs and PEEK are added to polytetrafluoroethylene for high-speed blending, and mixed at 1200r / min for 20 minutes by a high-speed mixer. Then the mixed powder is poured into a cold mold, and the powder is cold pressed at a pressure of 40-50MPa for 15-25min at room temperature. After the mixed powder is pressed, it is taken out of the cold mold, trimmed to remove burrs, and made smooth to obtain a composite sheet. Then it is placed in a sintering furnace for heat treatment. First, the temperature of the sintering furnace is increased from room temperature to 327°C at a heating rate of 1°C / min, and the sample is heat treated at 327°C for 60 minutes; then the temperature is increased to 375°C at a heating rate of 1°C / min and kept at this temperature for 90 minutes; then the temperature is cooled from 375°C to 327°C at a cooling rate of 1.5°C / min and kept at this temperature for 60 minutes; finally, after the insulation is completed, the power is turned off and the sample is allowed to cool naturally to room temperature; after the furnace temperature is cooled to room temperature, the heat-treated sheet is taken out of the furnace, and then a CNC machine tool is used to cut and prepare the sample to obtain a polytetrafluoroethylene composite material.
[0032] Embodiment 4:
[0033] Material ratio: 2wt% Ga / Al-LDHs, 20wt% PEEK and 78wt% polytetrafluoroethylene;
[0034] The preparation method of the modified polytetrafluoroethylene composite material is the same as that in Example 3.
[0035] Embodiment 5:
[0036] Raw material ratio: 4wt% Ga / Al-LDHs, 20wt% PEEK and 76wt% polytetrafluoroethylene;
[0037] The preparation method of the polytetrafluoroethylene composite material is the same as that in Example 3.
[0038] Embodiment 6:
[0039] Raw material ratio: 8wt% Ga / Al-LDHs, 20wt% PEEK and 72wt% polytetrafluoroethylene;
[0040] The preparation method of the modified polytetrafluoroethylene composite material is the same as that in Example 3.
[0041] After cooling to room temperature, the heat-treated sheet is taken out from the furnace to obtain a polytetrafluoroethylene composite material.
[0042] Embodiment 7:
[0043] Raw material ratio: 12wt% Ga / Al-LDHs, 20wt% PEEK and 68wt% polytetrafluoroethylene;
[0044] The preparation method of the modified polytetrafluoroethylene composite material is the same as that in Example 3.
[0045] Experimental Example 1: Tribological Test
[0046] The tribological test of the modified polytetrafluoroethylene composite materials of Examples 1 to 7 was carried out according to GB 3960-2016, with a load of 200 N, a rotation speed of 200 r / min, and a wear time of 2 h.
[0047] Under the same test conditions, the friction coefficient and wear rate of the pure polytetrafluoroethylene test sample are 0.184 and 16.517×10 -13 m 3 / Nm, the friction coefficient and wear rate of modified polytetrafluoroethylene composites with 0wt%, 1wt%, 2wt%, 4wt%, 8wt% and 12wt% Ga / Al-LDHs and 20wt% PEEK are shown in Figure 1 As shown in Table 1. Compared with pure PTFE, the addition of Ga / Al-LDHs and PEEK reduces the friction coefficient and wear rate of the modified PTFE composites, while the wear rate of the modified PTFE composites with 4wt% Ga / Al-LDHs and 20wt% PEEK is the smallest, only 0.067×10 -13 m 3 / Nm, therefore, in the subsequent experiments, 4wt% Ga / Al-LDHs was taken as a fixed amount, and PEEK and pure PTFE were taken as variables for performance research.
[0048] Table 1: Friction coefficient reduction and wear rate measurement values
[0049]
[0050]
[0051] Embodiment 8:
[0052] Raw material ratio: 4wt% Ga / Al-LDHs, 0wt% PEEK and 96wt% polytetrafluoroethylene;
[0053] Preparation method of modified polytetrafluoroethylene composite material: Ga / Al-LDHs is added to polytetrafluoroethylene for high-speed blending, and mixed at 1200r / min for 20 minutes by a high-speed mixer. Then the mixed powder is poured into a cold mold, and the powder is cold pressed at a pressure of 40-50MPa for 15-25min at room temperature. After the mixed powder is pressed, it is taken out of the cold mold, trimmed to remove burrs, and made smooth to obtain a composite sheet. Then it is placed in a sintering furnace for heat treatment. First, the temperature of the sintering furnace is increased from room temperature to 327°C at a heating rate of 1°C / min, and the sample is heat treated at 327°C for 60 minutes; then the temperature is increased to 375°C at a heating rate of 1°C / min and kept at this temperature for 90 minutes; then the temperature is cooled from 375°C to 327°C at a cooling rate of 1.5°C / min and kept at this temperature for 60 minutes; finally, after the insulation is completed, the power is turned off and the sample is allowed to cool naturally to room temperature; after the furnace temperature is cooled to room temperature, the heat-treated sheet is taken out of the furnace, and then a CNC machine tool is used to cut and prepare the sample to obtain a polytetrafluoroethylene composite material.
[0054] Embodiment 9:
[0055] Raw material ratio: 4wt% Ga / Al-LDHs, 5wt% PEEK and 91wt% polytetrafluoroethylene;
[0056] The preparation method of the modified polytetrafluoroethylene composite material is the same as that in Example 3.
[0057] Embodiment 10:
[0058] Raw material ratio: 4wt% Ga / Al-LDHs, 10wt% PEEK and 86wt% polytetrafluoroethylene;
[0059] The preparation method of the modified polytetrafluoroethylene composite material is the same as that in Example 3.
[0060] Embodiment 11:
[0061] Raw material ratio: 4wt% Ga / Al-LDHs, 30wt% PEEK and 66wt% polytetrafluoroethylene;
[0062] The preparation method of the modified polytetrafluoroethylene composite material is the same as that in Example 3.
[0063] Embodiment 12:
[0064] Raw material ratio: 4wt% Ga / Al-LDHs, 50wt% PEEK and 46wt% polytetrafluoroethylene;
[0065] The preparation method of the modified polytetrafluoroethylene composite material is the same as that in Example 3.
[0066] Experimental Example 2: Tribological Test
[0067] The tribological test of the modified polytetrafluoroethylene composite materials of Examples 8 to 12 was carried out according to GB 3960-2016, with a load of 200 N, a rotation speed of 200 r / min, and a wear time of 2 h.
[0068] The modified polytetrafluoroethylene composites with 0wt%, 5wt%, 10wt%, 20wt%, 30wt% and 50wt% PEEK and 4wt% Ga / Al-LDHs were subjected to tribological tests, and the tribological test results of Example 5 were taken for comparison. The friction coefficient and wear rate are shown in Figure 2 As shown in Table 2, the modified PTFE composite material with 4wt% Ga / Al-LDHs and 20wt% PEEK has the lowest wear rate.
[0069] Table 2: Friction coefficient reduction and wear rate determination values
[0070]
Claims
1. A wear-resistant modified polytetrafluoroethylene composite material, characterized in that: The modified polytetrafluoroethylene composite material is prepared by polytetrafluoroethylene filled with Ga / Al-LDHs and PEEK modified material; the Ga / Al-LDHs accounts for 1-12wt% of the total weight of the modified polytetrafluoroethylene composite material, the PEEK accounts for 5-50wt% of the total weight of the modified polytetrafluoroethylene composite material, and the polytetrafluoroethylene accounts for 94-38wt% of the total weight of the modified polytetrafluoroethylene composite material.
2. The wear-resistant modified polytetrafluoroethylene composite material according to claim 1, characterized in that: The Ga / Al-LDHs accounts for 1 to 8 wt % of the total weight of the polytetrafluoroethylene composite material, the PEEK accounts for 10 to 54 wt % of the total weight of the polytetrafluoroethylene composite material, and the polytetrafluoroethylene accounts for 89 to 38 wt % of the total weight of the polytetrafluoroethylene composite material.
3. The wear-resistant modified polytetrafluoroethylene composite material according to claim 1 or 2, characterized in that: The Ga / Al-LDHs accounts for 2-4wt% of the total weight of the polytetrafluoroethylene composite material, the PEEK accounts for 20-30wt% of the total weight of the polytetrafluoroethylene composite material, and the polytetrafluoroethylene accounts for 78-66wt% of the total weight of the polytetrafluoroethylene composite material.
4. The method for preparing the wear-resistant modified polytetrafluoroethylene composite material according to any one of claims 1 to 3, characterized in that: The preparation method is carried out according to the following steps: (1) Mixing: polytetrafluoroethylene, Ga / Al-LDHs and PEEK are mixed by a high-speed mixer at 1000-1400 r / min for 15-25 minutes to obtain product A; (2) Compression molding: Pour product A into a cold pressing mold and cold press the powder at room temperature at a pressure of 35 to 55 MPa for 10 to 30 minutes to obtain product B; (3) Thermal sintering treatment: Place product B in a sintering furnace, raise the temperature from room temperature to 322-332°C at a heating rate of 0.5-1.5°C / min, and keep it at 322-332°C for 55-65 min. Then, raise the temperature to 370-380°C at a heating rate of 0.5-1.5°C / min and keep it at that temperature for 80-100 min. Then, lower the temperature from 370-380°C to 322-332°C at a cooling rate of 1-2°C / min and keep it at that temperature for 55-65 min. After the heat preservation is completed, turn off the power supply, let it cool naturally to room temperature, and then cut and prepare the sample to obtain a polytetrafluoroethylene composite material.
5. The method for preparing the wear-resistant modified polytetrafluoroethylene composite material according to claim 4, characterized in that: In the step (1), mixing: polytetrafluoroethylene, Ga / Al-LDHs and PEEK are mixed by a high-speed mixer at 1200 r / min for 20 minutes to obtain product A.
6. The method for preparing the wear-resistant modified polytetrafluoroethylene composite material according to claim 4, characterized in that: In the step (2), compression molding: Pour product A into a cold pressing mold, and cold press the powder at a pressure of 40 to 50 MPa for 15 to 25 minutes at room temperature to obtain product B.
7. The method for preparing the wear-resistant modified polytetrafluoroethylene composite material according to claim 4, characterized in that: In the step (3), heat sintering treatment: take product B and place it in a sintering furnace, increase the temperature from room temperature to 327°C at a heating rate of 1°C / min, and keep it at 327°C for 60 minutes, then increase the temperature to 375°C at a heating rate of 1°C / min and keep it at that temperature for 90 minutes, then cool it from 375°C to 327°C at a cooling rate of 1.5°C / min and keep it at that temperature for 60 minutes, turn off the power after the insulation is completed, let it cool naturally to room temperature, and then cut and prepare samples to obtain a modified polytetrafluoroethylene composite material.
Citation Information
Patent Citations
Polytetrafluoroethylene composite material and preparation method thereof
CN103788551A
PEEK valve-plate composite material with high heat resistance and excellent wear resistance
CN105348772A
Modified PEEK (polyetheretherketone) material and preparation method of modified PEEK material
CN105440574A
Polyether ether ketone composite material preparation method
CN105733179A
Preparation method of montmorillonite-polyethersulfone-polytetrafluoroethylene self-lubricating composite material
CN116925484A
Cited By
Modified wear-resistant friction material for friction pendulum shock insulation support and preparation method of modified wear-resistant friction material
CN120365672A